2021
DOI: 10.1113/ep089180
|View full text |Cite
|
Sign up to set email alerts
|

Priming the cardiodynamic phase of pulmonary oxygen uptake through voluntary modulations of the respiratory pump at the onset of exercise

Abstract: We examined how different breathing patterns can modulate venous return and alveolar gas transfer during exercise transients in humans. Ten healthy men transitioned from rest to moderate cycling while breathing spontaneously (SP) or with voluntary increases in abdominal (AB) or intrathoracic (RC) pressure swings. We used double body plethysmography to determine blood displacements between the trunk and the extremities (V bs). From continuous signals of airflow and O 2 fraction, we calculated breath-by-breath o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 41 publications
2
6
0
Order By: Relevance
“…the increase in right ventricular filling would reduce left ventricular compliance) and increase afterload (Cheyne et al., 2020), although these effects remain unclear during exercise (Cheyne et al., 2018). In previous work, we found that during exercise, ‘abdominal’ and ‘rib cage’ breathing manoeuvres, designed to increase intra‐abdominal and intrathoracic pressure swings selectively by emphasizing the action of the diaphragm and the rib cage muscles, respectively, resulted in an increase in Vbs swings compared with spontaneous breathing (Stucky et al., 2021; Uva et al., 2016).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…the increase in right ventricular filling would reduce left ventricular compliance) and increase afterload (Cheyne et al., 2020), although these effects remain unclear during exercise (Cheyne et al., 2018). In previous work, we found that during exercise, ‘abdominal’ and ‘rib cage’ breathing manoeuvres, designed to increase intra‐abdominal and intrathoracic pressure swings selectively by emphasizing the action of the diaphragm and the rib cage muscles, respectively, resulted in an increase in Vbs swings compared with spontaneous breathing (Stucky et al., 2021; Uva et al., 2016).…”
Section: Discussionmentioning
confidence: 97%
“…Mathematical subtraction of the two signals yielded the volume of blood shifted between the trunk and the extremities (volume of blood shift; Vbs) (Aliverti et al, 2009(Aliverti et al, , 2010Uva et al, 2016;LoMauro & Aliverti, 2018;Stucky et al, 2021). Prior to the computation of Vbs, a validated algorithm was used to (1) correct the drift in the ∆Vb signal due to changes in thermodynamic conditions based on measured values of temperature and humidity and (2) automatically select the level of a wavelet filter applied to remove the remaining drift in ∆Vb due to numerical integration of the flow signal (Stucky et al, 2020).…”
Section: Computation Of Blood Shifts (Vbs)mentioning
confidence: 99%
“…Elegant physiologic experiments dating back to the 1950s have shown that the fall in ITP during normal inspiration produces a decrease in right atrial pressure and widens the pressure gradient from the peripheral venous circulation to the right atrium, thus augmenting venous return (28). With the RC breathing maneuver specifically, this seems to be the dominant mechanism, with more recent data confirming that deepening the inspiratory fall in ITP with RC breathing at rest augments femoral venous return (21) and results in greater intra-breath blood displacements between the trunk and the extremities during moderate exercise (23,25). With AB in turn, in addition to this ITP-driven increase in the venous pressure gradient, the inspiratory descent of the diaphragm may also contribute to augmented venous return via the consequent increase in IAP (29)(30)(31).…”
Section: Acute Cardiac Responses To Respiratory Maneuversmentioning
confidence: 98%
“…Previous experimental results suggested that voluntary amplification of the respiratory pump with AB and RC modulates femoral venous blood flow (21) and enhances blood displacements between the extremities and the trunk (22,23,25), indicating a potential for respiratory maneuvers to increase venous return. However, methodological constraints could not evaluate the impact of these interventions on cardiac function per se.…”
Section: Acute Cardiac Responses To Respiratory Maneuversmentioning
confidence: 99%
See 1 more Smart Citation